x+2(x+1)=122-3(x+2)

Simple and best practice solution for x+2(x+1)=122-3(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+2(x+1)=122-3(x+2) equation:


Simplifying
x + 2(x + 1) = 122 + -3(x + 2)

Reorder the terms:
x + 2(1 + x) = 122 + -3(x + 2)
x + (1 * 2 + x * 2) = 122 + -3(x + 2)
x + (2 + 2x) = 122 + -3(x + 2)

Reorder the terms:
2 + x + 2x = 122 + -3(x + 2)

Combine like terms: x + 2x = 3x
2 + 3x = 122 + -3(x + 2)

Reorder the terms:
2 + 3x = 122 + -3(2 + x)
2 + 3x = 122 + (2 * -3 + x * -3)
2 + 3x = 122 + (-6 + -3x)

Combine like terms: 122 + -6 = 116
2 + 3x = 116 + -3x

Solving
2 + 3x = 116 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
2 + 3x + 3x = 116 + -3x + 3x

Combine like terms: 3x + 3x = 6x
2 + 6x = 116 + -3x + 3x

Combine like terms: -3x + 3x = 0
2 + 6x = 116 + 0
2 + 6x = 116

Add '-2' to each side of the equation.
2 + -2 + 6x = 116 + -2

Combine like terms: 2 + -2 = 0
0 + 6x = 116 + -2
6x = 116 + -2

Combine like terms: 116 + -2 = 114
6x = 114

Divide each side by '6'.
x = 19

Simplifying
x = 19

See similar equations:

| -8(m+1)-m-12=-9(m+4)+16 | | x+(x-3)=9 | | -8=m/6-9 | | -7(2b+2)+15b-8=0 | | 2/3*2 | | 7x+5=4x+9 | | 8-x=4x+8 | | 512/252 | | 2x-11=1x+11 | | -2x^2-3x-9=0 | | 2x-2y*1=-4*1 | | 11(v+1)-3v=4(2v+4)-24 | | m/7+4=3m | | 55=6000/12(r) | | 9x-(5x+7)=6x-13 | | 3.8q-5.7-4.3q=-1.5q-211 | | 4+(-50)= | | 50+10n=180 | | 8x+11=2x+65 | | c=2(4c+7) | | -7(v+3)+3v+5=8v+8 | | 3+3x-6x^2=0 | | t+3+(8/t)=0 | | -4=a-10/3 | | 16+19(167x)=1132 | | x^2+18x+80=143 | | 4c-6+2c=20 | | -3(t-5)+5t=9t-4 | | 7=z/43 | | 15x^2-13=8 | | (6n+12)+(3n+6)=58.5 | | -0.166667(x-12)+0.333333(x+3)=x-12 |

Equations solver categories